Soroban as a learning strategy in basic mathematical operations (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2018)
The purpose was to promote the Soroban as a learning strategy for basic mathematical operations among first-grade children at the Comfanorte School in the municipality of Los Patios, Norte de Santander. The methodology was the positivist paradigm, quantitative approach, descriptive type, non-experimental transactional field design. The population consisted of three teachers and 30 children. The data were tabulated and coded manually, applying descriptive statistical criteria to enable analysis and discussion by dimension. It was concluded that the subjects claimed to be unaware of the usefulness of the Soroban as a learning strategy and how easy it would make learning mathematics.